Study on pattern of consumption of fruits and vegetables and associated factors among medical students of Delhi - Khokhar, Anita; Singh, Sunil Kumar; Bharti, Aakanksha; Sharma, Manila; Mishra, Suruchi (International Journal of Research in Medical Sciences, 2021)
Background: Fruits and vegetables are a rich source of essential micronutrients i.e. vitamins/minerals and dietary fibers required for the normal daily functionality of the body. Young adults such as medical students are a particularly vulnerable population in terms of health issues and adequate diet. Objective of the study was to find the pattern of fruits and vegetables consumption in undergraduate medical students of Delhi. Methods: A cross-sectional study was planned among 300 undergraduate students from medical college in New Delhi. The questionnaire consisted of questions about identification data, pattern of fruit and vegetable consumption. Data was analyzed by SPSS software version 21.0 and for qualitative data analysis chi-square test was used. Results: Mean age of study subjects was 20.82±2.1 years and females (52.7%) were more as compared to (47.3%) males. Out of 300 participants, only one third (33.3%) of study participants consumed more than five servings of fruits and vegetables. More than half of study participants felt that unsafe use of pesticides, difficult to eat five servings in a day, poor handling and poor quality of fruits and vegetables were the most common barriers in consumption of FVs. Age and semester of study participants and education status of mothers were found significant predictors of consumption of recommended number of serving of FVs in day. Conclusions: This study concludes that only one third of study participants consumed more than five servings of fruits and vegetables which is recommended number of serving in a day. So, there is a need to increase awareness about importance of fruits and vegetables consumption among study population.